PERAN TEKNOLOGI BLOCKCHAIN DALAM MENINGKATKAN KEAMANAN DAN KEPASTIAN HUKUM DALAM TRANSAKSI KONTRAK DI INDONESIA - Leny Megawati; Cecep Wiharma; Asep Hasanudin (Universitas Suryakancana, 2023)
Indonesia has experienced rapid growth in the technology sector and digital economy. However, traditional contract transactions still often face problems such as legal uncertainty, fraud and complicated bureaucracy. The blockchain technology system brings major changes in various sectors, including in the context of security and legal certainty in contract transactions in Indonesia. The problem that will be discussed in this research is, How can blockchain technology be used to increase transparency and data integrity in contract transactions in Indonesia? Are there any legal regulations governing the use of blockchain technology in contract transactions in Indonesia? How does the application of blockchain technology in contract transactions in Indonesia affect the resolution of contract disputes? The approach method that the author uses in this research is a normative juridical approach. In this research, the author studies legal rules by examining statutory regulations and legal concepts that are related to this research. Based on the research results, it can be seen that in general, the role of blockchain technology in increasing security and legal certainty in contract transactions in Indonesia is very important in facing challenges related to reliability, security and legal certainty that are often faced in conventional systems.Keywords: Blockchain; Contract; Security.